Estudo da reação foto-fenton induzida por compexos de FE(III)+EDTA para o tratamento de lixiviados de aterros sanitários - Fernandes, Édina Jaíne (2017)
The present work aims to study the induced photo-Fenton reaction with an organic complexant, EDTA, in order to determine the best conditions for the treatment of landfill leachate (LAS), since that application of conventional photo-Fenton reaction generates some inconveniences, such as acidification of the solution, leading to the reduction of the organic compounds. The reactions of the F-Fenton-EDTA process were carried out in a photoreactor called SUNTEST, laboratory scale, in batch system with recirculation. The operating parameters of the process, such as pH of the solution, iron ion and EDTA concentrations, H 2 O 2 consumption, and the amount of UV energy required for the reduction of color and aromatic compounds (λ 254 nm) in the LAS. The best results were obtained employing concentrations of 90 mg of Fe(III) L -1 and solution pH 7,8, as it allowed the pollutants to remain in the LAS, being available for oxidation, besides keeping the iron ions dissolved, providing a favorable reaction medium for the oxidative process. Thus, approximately 40% reduction in color and aromatic compounds (λ 254 nm) was obtained, consuming about 6.400 mg H 2 O 2 L -1 and requiring 8,9 Q UV kJ L -1 energy. Thus, it can be observed that the F-Fenton- EDTA process presents itself as an alternative for the mineralization of contaminants found in the LAS, minimizing the environmental impacts resulting from the inadequate discharge of this material into the recipient bodies.